FINANCIAL RATIO ANALYSIS AT PT PHAPROS TBK - Ari Kharisma (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the financial performance of PT Phapros Tbk in the period 2021-2023 using financial ratios. This study uses quantitative data. The data source used is secondary data in the form of financial reports consisting of the financial position report and profit and loss report of PT Phapros Tbk. The financial reports were obtained from the official website of PT Phapros Tbk and the Indonesia Stock Exchange (IDX). The results of this study are the financial performance of PT Phapros Tbk, for the liquidity ratio with the current ratio, quick ratio, and cash ratio methods show poor results because the company has not been able to pay off short-term debts at the specified time. The Solvability Ratio with the Debt to Asset Ratio and Debt to Equity Ratio methods shows poor results because the company's funding is financed by debt. The Profitability Ratio with the Net Profit Margin, Return on Assets, and Return on Equity methods shows poor results because the company has not been efficient in maximizing profits from production costs and assets owned. Activity ratio with Inventory Turnover, Fixed Assets Turnover, and Total Assets Turnover methods shows less than satisfactory results because the company does not use assets optimally to generate revenue.